The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1089/ars.2012.5068
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis: Molecular Mechanisms and Therapeutic Opportunities

Abstract: The pathophysiology of multiple sclerosis (MS) involves several components: redox, inflammatory/autoimmune, vascular, and neurodegenerative. All of them are supported by the intertwined lines of evidence, and none of them should be written off. However, the exact mechanisms of MS initiation, its development, and progression are still elusive, despite the impressive pace by which the data on MS are accumulating. In this review, we will try to integrate the current facts and concepts, focusing on the role of red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 492 publications
(641 reference statements)
1
77
0
2
Order By: Relevance
“…Finally, EP and DMF are capable of providing a more direct antioxidative protection via scavenging superoxide and hydroxyl radical, which have the central place in MS-related neurodegenerative processes, such as "slow burning" of demyelinated neurons and oxidative damage directly inflicted by cytotoxic cells (5). Emerging data imply that EP might be an effective antiinflammatory agent in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, EP and DMF are capable of providing a more direct antioxidative protection via scavenging superoxide and hydroxyl radical, which have the central place in MS-related neurodegenerative processes, such as "slow burning" of demyelinated neurons and oxidative damage directly inflicted by cytotoxic cells (5). Emerging data imply that EP might be an effective antiinflammatory agent in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of DMF appears to be prevalently based on redox properties, that is, binding to thiols via Michael-type addition (3). DMF turns off thiol redox switches on T cell membrane, whereas in neurons and astrocytes, DMF targets specific thiol moieties, which leads to activation of Nrf2-controled set of antioxidative enzymes, NAD(P)H: quinine oxidoreductase 1 and glutathione-related enzymes, and downregulation of transcription factor NF-kB (2,4,5). These pharmacological strategies-targeting of redox switches to suppress T cell activity (6)(7)(8), and activation of endogenous antioxidative system instead of frequently futile application of exogenous antioxidants (9)-are rather new and hold promise of further therapeutic relevance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It seems T H 1 and T H 17 cells are the main pathogenic populations in the immunopathogenesis of MS (Jadidi-Niaragh & Mirshafiey 2011b). Although there are no DC in a healthy CNS, other antigen-presenting cells (APC) like macrophages, microglia, B cells, endothelial cells and astrocytes can prime autoreactive Tcells at the disease initiation stage (Ransohoff & Engelhardt 2012;Miljković & Spasojević 2013;Yazdani et al 2013). Interestingly, it was reported that microglia and macrophages could differentiate into DC-like cells (Ponomarev et al 2005).…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…The cleavage of extracellular matrix by these enzymes not only damages the CNS parenchyma and BBB integrity, but also creates several protein fragments, which may act as chemoattractants and immunomodulators (Weathington et al 2006). Altogether, these events disturb BBB integrity and recruit various leukocytes into the CNS (Miljković & Spasojević 2013) (Figure 1).…”
Section: Multiple Sclerosismentioning
confidence: 99%